ALBANIA’S QUEST FOR A SECURTY GUARANTOR - Pavlović, Đorđe (National interest, 2025)
In the paper, the author tries to present Albania’s experiences with the selection of a strategic security guarantor, with a special focus on her expertise related to NATO from 1992 onwards. The central hypothesis of this research is that the Albanian state has benefited from the extended deterrence provided by NATO not only after it became a member of that alliance in 2009 but even more than a decade before that. In this context, the author will focus on two examples, the first of which refers to the situation in which Albania found itself during the NATO aggression against the Federal Republic of Yugoslavia in 1999. The second indicates how the Albanian state benefited from the Alliance’s expansion in the Western Balkans to improve the protection of the Albanian population in the neighborhood. In addition, the paper will also present specific ways in which Albania is seeking to improve its position within NATO so that the extended deterrence provided by that alliance can contribute as much as possible to the protection of Albanian national interests. The dominant data source for this work is scientific literature, while comparative and historical methods and case studies were used to draw conclusions.